(untitled) (Journal of Health Sciences, 2019)
Introduction: Occupational stress is inevitable, but prolonged and intense can lead to serious health problems. Neglecting this significant aspect of work and inadequate treatment of the first indicators results in the reduced working capacity of healthcare professionals. Material and methods: Assessing working conditions of 100 healthcare professionals regarding stress impact on empathy and workability was the primary goal of this study. A survey was conducted to identify differences between work in intensive care units and other clinical departments all related to empathy, workability, and stress perceiving to determine what is a better predictor of workability. Results: In the research group “intensive care units”, significantly lower empathy quotients, poorer workability, and different stressors were registered compared to research groups named “other departments”. Conclusion: The main conclusion of the study states different dynamics in the working environment of intensive care units compared to other departments that could potentially harm the personal capacity of healthcare professionals.